Transformation of emotional intelligence: Generate the first class human capital among youth - Johar, Siti Sarawati; Ani, Fauziah; Halim, Harliana; Hamzah, Shahidah; Zainol, Nur Zainatul Nadra; Saparudin, Intan Farhana; Abdul Rahman, Siti Aisyah Panatik; Raja Ibrahim, Raja Zirwatul Aida (American Scientific Publishers, 2018)
This paper focuses on discussing the importance of strengthening emotional intelligence among youths to achieve more integrated human domains. The discussion is in terms of impact, challenges and needs of the transformation of emotional intelligence to the positive mind and behaviour. Human capital resources among youths are the main thrusts of national development especially from political, economic, social and educational aspects. However, the role of youth as agents of change in society would be meaningless if it is a transformation from darkness to brightness, from positive to negative and from peace to chaos. Important elements that need to be as knowledgeable youth are not merely intellectual intelligence, but also the need for strong emotional and spiritual intelligence to achieve positive emotional, positive thinking and behaviour. Emotional intelligence can be a determining factor in behaviour and ideology that is more mature and prosperous among the youth of the country. Therefore, the need to have emotional intelligence is as important as the intellectual intelligence to achieve a real balance in life. Positive youth can stand up as a citizen who is full of identity and dare to cope with the competitive world, but also wisely handle whatever challenges. A strong emotional intelligence in the youth can also help transform the country's expectation into reality in the quest for the creation of a first-class human capital